A study on status of senior citizen of Kathmandu metropolitan city, Kathmandu, Nepal. - Rana, Ramesh (2008)
ABSTRACT: Senior citizen with sixty years and above is a rapidly expanding segment of population of Nepal. The traditional extended family is being transformed into the nuclear family which has resulted in the marginalization and, in some case, complete abandonment of a great number of our seniors and exclusion in many activities. The study entitled " Status of Senior Citizen of Kathmandu Metropolitan City, Nepal" was carried out from August 2007 to January 2008 to identify the socio - economic status of senior citizens, to find out health problems of senior citizens and to reveal interest and need of senior citizens. It was descriptive type of study based on primary data collected from 188 senior citizens who were selected purposively. The data collection tools were pre-tested interview schedule and Focus Group Discussion Guidelines. The major health problem for male was Asthma (18.5%) followed by Hypertension (17.7%), Gastritis or abdominal problems (10.5%) whereas major health problems for female were Hypertension (21.2%) followed by Asthma (17.6%), Gastritis or abdominal problems (9.6%) . The major health problem of senior citizen of 70 years was Asthma and the major health problems of majority of senior citizens with 71 and above years was Hypertension. Hospital was treatment center for more than half of male (50.6%) and female (54.5%). The median expenditure for treatment per month was Rs. 500. Main source for fund were pension, family members and occupation in which they have involved. Male and Female smokes 5.39 and 4.18 cigarettes per day. Less than five percent male (3.2%) and female (4.7%) were living with other than family. About 15 Percent senior male had desire to remarry. Religious activities are major concern to pass time for about half of male (46.8%) and female (45.3%). About two times more female (51.6%) than male (32.3%) had no desire, will and interest to fulfill. Majority of male (39.6%) and female (29.7%) had love and affection to their wife/husband and majority also received love from their wife and husband. A very vast majority senior citizen was included in decision making process of family and instruction ad suggestions delivered among family members was found to be followed. Male spend his longest time with his wife (58.1%) followed by grandchildren (18.5%), son (11.3%) and daughter (9.7%) and female spend her longest time with her grandchildren (39.1%) followed by husband (29.7%), daughter (10.9%) and son (7.8%). Senior citizens have Asthma and Hypertension as the major health problems. Their need and interest is to be religious. Their views and ideas are neglected in their family so that it is necessary to manage hospital treatment in free of cost to minimize complexity of health problems and Advocacy and informative type of program on behalf of senior citizens should be developed to sensitize families and communities.